2017
DOI: 10.1007/s00216-017-0312-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tetrabromobisphenol A and its mono- and dimethyl derivatives in fish, sediment and suspended particulate matter from European freshwaters and estuaries

Abstract: An analytical method was developed for the determination of tetrabromobisphenol A (TBBPA), 3,3′,5,5′-tetrabromobisphenol-A-monomethyl ether (MM-TBBPA) and 3,3′,5,5′-tetrabromobisphenol-A-dimethyl ether (DM-TBBPA), and its valid application on fish muscle matrix (bream and sole), suspended particulate matter (SPM) and surface sediment layer samples, using only 0.5 g sample material, is demonstrated. Here, for the first time, DM-TBBPA could be determined by an LC-MS/MS-based method applying atmospheric pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 28 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…For example, the concentrations of TBBPA and TBBPA DME in surficial sediments were 34 and 24 ng g −1 dry weight (dw) upstream and 270 and 1500 ngg −1 dw downstream of a plastic factory, respectively (Sellström and Jansson,1995). It was also reported that TBBPA MME showed higher concentrations than TBBPA in some fish (Kotthoff et al, 2017). Even in some samples, such as those in mussels and peregrine falcon ( Falco peregrinus ) eggs, only TBBPA DME was detectable without measurable TBBPA (Watanabe et al, 1983; Vorkamp et al, 2005).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…For example, the concentrations of TBBPA and TBBPA DME in surficial sediments were 34 and 24 ng g −1 dry weight (dw) upstream and 270 and 1500 ngg −1 dw downstream of a plastic factory, respectively (Sellström and Jansson,1995). It was also reported that TBBPA MME showed higher concentrations than TBBPA in some fish (Kotthoff et al, 2017). Even in some samples, such as those in mussels and peregrine falcon ( Falco peregrinus ) eggs, only TBBPA DME was detectable without measurable TBBPA (Watanabe et al, 1983; Vorkamp et al, 2005).…”
Section: Introductionmentioning
confidence: 86%
“…TBBPA DME and TBBPA MME have been detected together with TBBPA in aquatic systems, sediments and animals (Watanabe et al, 1983; Sellström and Jansson, 1995; Vorkamp et al, 2005; Kotthoff et al, 2017). TBBPA generally exhibits higher concentrations in the environment than TBBPA DME and TBBPA MME.…”
Section: Introductionmentioning
confidence: 99%
“…In recently published data from our own research, we exposed zebrafish embryos to THDCs with different modes of action: propylthiouracil (PTU), a pharmaceutical that inhibits TH synthesis [17], and tetrabromobisphenol-A (TBBPA), a flame retardant that has been reported to interact with TH receptors [18,19]. Moreover, the interaction of TBBPA with binding proteins and hepatic clearance have been reported [4], as well as competitive binding to the plasma-transporter protein of T4, transthyretin [18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the interaction of TBBPA with binding proteins and hepatic clearance have been reported [4], as well as competitive binding to the plasma-transporter protein of T4, transthyretin [18]. The pharmaceutical PTU was selected as a typical positive reference substance, while TBBPA is environmentally relevant with concentrations of up to 2.6 μg kg −1 dry weight in sediment samples and up to 1.2 μg kg −1 wet weight in fish [19]. Measurements from different English lakes revealed that concentrations of TBBPA range from 140 to 3200 pg L −1 (water), 330 to 3800 pg g −1 dry weight (sediment), and <0.29 to 1.7 ng g −1 lipid weight (fish) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Greater recovery (84.2–88.6%) was obtained by Erarpat et al (2019) possibly due to the derivatization process and the greater sample volumes reported by these authors to determine organotin compounds in fish and mussel samples. Generally, extraction methods for environmental matrices such as wastewaters, sludge, animal tissues, and aquatic organisms require more robust and expensive techniques, using greater volumes of organic solvents and longer sample preparation times (Zhang et al 2016; Kotthoff et al 2017; Liu L. et al 2017). Most environmental samples are pretreated or extracted with conventional procedures such as SPE or liquid phase extraction, leading to excellent results (Saint‐Louis and Pelletier 2004; Kabir et al 2017; Burato et al 2020).…”
Section: Resultsmentioning
confidence: 99%